2022
DOI: 10.1088/2051-672x/ac9acd
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mass conservation cavitation boundary on the tribo-dynamic responses of the micro-groove water-lubricated bearing

Abstract: This study aims to reveal the role of the mass conversation cavitation boundary on the tribo-dynamic responses of five kinds of micro-groove water-lubricated bearing under mixed lubrication. By introducing the mass conservation boundary, the tribo-dynamic model of the water-lubricated micro-groove bearing is established and numerically solved by the control volume method. The accuracy of the developed model is verified by comparing the calculated results with the existing experimental and simulation results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Subsequently, Jin et al [40] evaluated the tribological properties of bearings, and compared the effect of the bottom profiles of the micro-groove on the wear of bearings. Cai et al [41] compared the impact of cavitation on the performance of different micro-groove bearings for Reynolds boundary condition and mass conservation boundary condition, and found that cavitation stabilized journal motion and enhanced the hydrodynamic effect for micro-groove bearings. Li et al [42,43] recently adopted the mass conservation boundary condition to analyze the lubrication performance of water-lubricated micro-groove bearings (WLGBs) considering turbulence and journal misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Jin et al [40] evaluated the tribological properties of bearings, and compared the effect of the bottom profiles of the micro-groove on the wear of bearings. Cai et al [41] compared the impact of cavitation on the performance of different micro-groove bearings for Reynolds boundary condition and mass conservation boundary condition, and found that cavitation stabilized journal motion and enhanced the hydrodynamic effect for micro-groove bearings. Li et al [42,43] recently adopted the mass conservation boundary condition to analyze the lubrication performance of water-lubricated micro-groove bearings (WLGBs) considering turbulence and journal misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the research described above, many studies [16][17][18][19][20][21][22][23][24][25][26][27][28] on wear, dynamic characteristics, friction-induced vibration and noise of water-lubricated stern tube bearings have also been conducted by scholars. Han et al [16] experimentally studied the mechanism of action of stick-slip nonlinear friction-induced vibration of water-lubricated stern rube bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [24] numerically explored the effects of wear and shaft shape error defects on the tribo-dynamic responses of water-lubricated bearings under non-linear propeller disturbance, and the results showed that the nonlinear disturbance had a significant influence on the dynamic behavior, and the use of reasonable wear parameters can improve the lubrication performance. Subsequently, they updated the tribo-dynamic model in order to consider mass conservation cavitation, and conducted an investigation on micro-groove water-lubricated bearings [25]. Recently, they proposed a new mathematical modeling technique to investigate the nonlinear dynamic mixed friction behaviors of journal-thrustcoupled bearings lubricated with water [26].…”
Section: Introductionmentioning
confidence: 99%
“…Tribological performance of friction surfaces may be enhanced by the surface texturing method, which involves embedding pits on the sliding surface contact (Aiman et al , 2021). By conserving lubrication, trapping worn debris, reducing the contact surface and generating hydrodynamic pressure, micro-pits technology may enhance anti-seizing performance (Cai et al , 2022). Researchers have shown that the texture of the mating surface between two metals may have a significant effect on the impact of the interaction (Nsilani Kouediatouka et al , 2022).…”
Section: Introductionmentioning
confidence: 99%